Sistem Informasi Akademik Pada SMA Muhammadiyah 2 Palembang - M. Afdhaluddin (Pusat Riset dan Inovasi Nasional, 2023)
Palembang Muhammadiyah 2 High School is one of the upper secondary schools, which will continue to grow in order to improve the competence and quality of its students. But there are still some obstacles in the management of academic data which still uses paper based as an archive. The purpose of this thesis is to build an academic information system at Muhammadiyah 2 High School Palembang to simplify and save time in the process of selecting teacher teaching schedules, final grades, search for teacher and student data and attendance recap. Where the design of this information system can be used as a medium to help information systems become more effective and efficient. The system was built using an iterative development methodology and using the PHP programming language and MySQL as a DBMS. With the application can help the business administration in the recap of attendance, grades, SPP monitoring, data search for teachers and students in Palembang Muhammadiyah 2 High School.